SOCIAL STUDIES TEACHERS’ PROCLIVITIES TO TEACH WORLD HISTORY IN THE NEW K TO 12 – JUNIOR HIGH SCHOOL CURRICULUM IN THE PHILIPPINES - Reynaldo B. Inocian (European Scientific Journal, ESJ, 2014)
According to George Lucas, “The one way the world hasn’t changed: Teaching is the most important job.” This supports the profession’s nobility—that without it there could be no other professionals around. This qualitative study assessed the social studies teachers’ proclivities to teach world history, by (1) analyzing their learning styles and their likelihood to teach using the brain quadrants; (2) describing the actual demonstration based on selected lessons in each unit of work, and (3) generating themes based on their values, expressions, impressions and written commitments. The study employed a typical case analysis of a selected cluster of Social Studies teachers, among the five city divisions in Cebu, who attended the Grade 9 Mass Training for Social Studies in summer, 2014. A researchermade- questionnaire, designed according to the Ned Hermann’s Brain Quadrants, was administered before the start of the training. Narratives on their challenging moments during the five-day training-workshop were generated, clustered and analyzed. Actual observations on their attendance, participation in break-out and plenary sessions and teaching demonstrations were also observed. Significant insights, expressions, impressions, and personal commitments were recorded. Their proclivities to teach world history before and during the training were consistent with their behavior and performance as shown in the actual planning and teaching demonstration on the KPUP Model of Teaching. Receptiveness, cautious assessment, holistic teaching, dynamic synergy, candidness, sincerity, and honest commitments were useful themes that consequently generated the values of self-regulation, extraversion, agreeableness and openness (Mirhashemi & Goodarzi, 2014) for the successful implementation of the K to 12. At the outset, not one of the groups in the cluster showed a perfect whole brain propensity to teach world history—a challenge that they needed to address right after the training.